STUDENTS’ CHEMICAL LITERACY PROFILE ON CHEMICAL EQUILIBRIUM MATERIAL: A CASE OF CORAL REEFS TOPIC - Pratama, Faiz Ilham; Rohaeti, Eli; Laksono, Endang Widjajanti (Universitas Labuhanbatu, 2024)
Nowadays, chemical literacy is something important to discuss, including the benefits of chemical literacy itself. It can be the main purpose for teachers, experts, and curriculum policymakers. Chemical literacy is necessary for students since it can be a background for them to make a decision, build their critical thinking, and creativity, and help them solve daily problems or natural phenomena based on their knowledge. This research aimed to describe the students’ chemical literacy profile on chemical equilibrium materials in coral reef topics. The research question posed in this study is